2011
DOI: 10.1182/blood-2010-12-322339
|View full text |Cite
|
Sign up to set email alerts
|

CD48 on hematopoietic progenitors regulates stem cells and suppresses tumor formation

Abstract: The proliferation and differentiation of adult stem cells is balanced to ensure adequate generation of differentiated cells, stem cell homeostasis, and guard against malignant transformation. CD48 is broadly expressed on hematopoietic cells but excluded from quiescent longterm murine HSCs. Through its interactions with CD244 on progenitor cells, it influences HSC function by altering the BM cytokine milieu, particularly IFN␥. In CD48-null mice, the resultant misregulation of cytokine signaling produces a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
(63 reference statements)
2
24
0
Order By: Relevance
“…The dose-dependent induction of AIF was conserved across multiple probe sets and is consistent with the MRI data described above suggesting early vascular trauma. CD48, a plasma membrane immunoglobulin, is intimately involved in immune signaling and has been reported to act as a regulator that inhibits the malignant transformation of stem cells 18 . Finally, CCR1, a G-protein coupled plasma membrane receptor, is a known mediator of host immune response with a potential role in the induction of apoptotic cell death 19 .…”
Section: Resultsmentioning
confidence: 99%
“…The dose-dependent induction of AIF was conserved across multiple probe sets and is consistent with the MRI data described above suggesting early vascular trauma. CD48, a plasma membrane immunoglobulin, is intimately involved in immune signaling and has been reported to act as a regulator that inhibits the malignant transformation of stem cells 18 . Finally, CCR1, a G-protein coupled plasma membrane receptor, is a known mediator of host immune response with a potential role in the induction of apoptotic cell death 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Boles et al observed altered distribution of monocyte and lymphocyte precursors in the bone marrow of CD48−/− [B6.129] mice and a reduced proliferative capacity of CD48−/− HSCs. Aged CD48−/− mice had an increased incidence of lymphoma, which correlated with upregulated Pak1 activity in CD19+ tumor cells but not in CD19+ cells from the spleen [122]. Whether altered hematopoiesis and increased incidence of tumors in CD48−/− [B6.129] mice is due to CD48 intrinsic effects, or interactions between 129- and B6-derived genes, remains to be determined.…”
Section: Immunoregulatory Roles For Cd48 Determined By Studies In mentioning
confidence: 99%
“…Utilizing the Shb knockout mouse [30], we find in the current study reduced bone marrow cell responsiveness to SCF-stimulation and elevated basal activity with respect to the FAK/Rac1/p21-activated kinase (PAK) signaling axis [11,28,31], proliferation defects in LT-HSCs during homeostasis, and an impairment in the long-term myeloid repopulating capacity of LT-HSCs. Unexpectedly, Shb is dispensable for stress hematopoiesis, and its loss results in diminished myelodepression in a non-competitive hematopoietic environment after genotoxic stress.…”
Section: Introductionmentioning
confidence: 96%
“…Signaling through FAK/Rac1/PAK has been implicated in LT-HSC and HPC cell cycle control, thus providing a mechanistic explanation for the observed differences in the LT-HSC cell cycle [10,11,28,31,43].…”
Section: Altered Signaling Characteristics In Shb Knockout Bone Marromentioning
confidence: 99%
See 1 more Smart Citation